Two cases of WWTR1-CAMTA-1 fusion-positive epithelioid hemangioendotheliomas with extremely different outcomes - Yoshitane Tsukamoto; Hiroyuki Futani; Takahiro Watanabe; Kazutake Kemmoku; Takanori Iwayama; Shohei Matsuo; Seiichi Hirota; Shinichi Yoshiya (Elsevier, 2018)
We report two cases of WWTR1-CAMTA1 fusion-positive epithelioid hemangioendotheliomas (EHEs) with extremely different clinical behaviors. The first case was a 52-year-old Japanese woman with a complaint of an enlarging right axillary mass. Surgical specimen showed that the epithelioid tumors within the vein had the pathological feature of a cord-like pattern with myxoid or hyaline matrix and the intracytoplasmic lumen with erythrocytes and the immunophenotype of endothelial cells. The final pathological diagnosis was classic EHE. An RT-PCR analysis showed positivity of WWTR1-CAMTA1 fusion. The patient has now been free of disease for 7 years after surgery. The second case was a 70-year-old Japanese male with a complaint of severe pain of his left thigh. The radiographic findings showed ectopic calcification near the left femur. Surgical specimen showed clusters of malignant epithelioid cells with necrosis and obvious mitoses in soft tissue. They were also shown to be of endothelial origin by immunohistochemistry (IHC). The pathological diagnosis was malignant EHE or epithelioid angiosarcoma with ectopic ossification. An RT-PCR analysis showed the tumor had WWTR1-CAMTA1 fusion. Thus, the final pathological diagnosis was malignant EHE. Unfortunately, he died 7 months after surgery due to pleural dissemination. Although fusion gene is thought to define one spectrum of specific tumors, our two cases of EHEs with WWTR1-CAMTA1 fusion showed extremely different outcomes, one is rather benign and the other fatal. Retrospective study showed that both tumors were positive for nuclear CAMTA1 by IHC. Fusion-genes define a unique spectrum of tumors, but even in the tumors within the same spectrum defined by a specific fusion-gene, there are heterogeneities of malignant potentials. Therefore, factors other than fusion-genes may contribute to prognoses. Keywords: Epithelioid hemangioendothelioma, WWTR1-CAMTA1 fusion, CAMTA1 immunohistochemistry, Ossification